Sphingosines Derived from Marine Sponge as Potential Multi-Target Drug Related to Disorders in Cancer Development - Biegelmeyer, Renata (Mar Drugs, 2015)
Haliclona tubifera, marine sponge species abundant in Brazilian coastline, presents only a few papers published in the literature. Recently, we have reported the isolation of two modified C18 sphingoid bases: (2R,3R,6R,7Z)-2-aminooctadec-7-ene-1,3,6-triol and and (2R,3R,6R)-2-aminooctadec-1,3,6-triol. In order to continue our research, in this work aimed at the biological investigation of fractions that led to the isolation of these compounds. We evaluated the cytotoxic effect of marine sponge H. tubifera fractions in glioma (U87) and neuroblastoma (SH-SY5Y) human cell lines. In addition, considering the link between cancer, imbalance of reactive oxygen species and coagulation disorders, we also investigated the in vitro effects on blood coagulation and their redox properties. We showed that the ethyl acetate (EtOAc) fraction, rich in sphingoid bases, had important cytotoxic effects in both cancer cell lines with an IC(50) < 15 μg/mL and also can inhibit the production of peroxyl radicals. Interestingly, this fraction increased the recalcification time of human blood, showing anticoagulant properties. The present study indicates the sphingosines fraction as a promising source of chemical prototypes, especially multifunctional drugs in cancer therapy.